Chain‐growth condensation polymerization approach to synthesis of well‐defined polybenzoxazole: Importance of higher reactivity of 3‐amino‐4‐hydroxybenzoic acid ester compared to 4‐amino‐3‐hydroxybenzoic acid ester. Issue 12 (3rd April 2014) - Ohta, Yoshihiro; Niiyama, Tetsurou; Yokoyama, Akihiro; Yokozawa, Tsutomu
ABSTRACT Application of chain‐growth condensation polymerization (CGCP) to obtain well‐defined polybenzoxazole (PBO) was examined. CGCP of both phenyl 3‐(2‐methoxyethoxy)methoxy (MEM‐oxy)‐4‐(octylamino)benzoate (1b) (para‐substituted monomer) and phenyl 4‐MEM‐oxy‐3‐(octylamino)benzoate (3b) (meta‐substituted monomer) was examined in the presence of metal disilazide base and phenyl 4‐nitro‐ or methylbenzoate 2 as an initiator. Polymerization of the latter monomer, but not the former, afforded polymer with controlled molecular weight based on the feed ratio of monomer to initiator and with a narrow molecular weight distribution. Accordingly, monomer 3c, in which the octyl group on the amino nitrogen of 3b was replaced with a 4‐(octyloxy)benzyl (OOB) group, was polymerized in the presence of lithium 1, 1, 1, 3, 3, 3‐hexamethyldisilazide (LiHMDS), phenyl 4‐methylbenzoate (2b), and LiCl in THF at 0 °C to yield poly3c with well‐defined molecular weight (Mn = 4520–9080) and low polydispersity (Mw/Mn ≤ 1.11). Treatment of poly3c with trifluoroacetic acid simultaneously removed the MEM and OOB groups, affording poly(o‐hydroxyamide) (poly4) without scission of the amide linkages. Cyclodehydration of poly4 proceeded at 350 °C to yield PBO (poly5), which was insoluble in organic solvents and acids. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1730–1736